Une analyse économétrique du comportement d’intermédiation financière des sociétés de crédit populaire : le cas des caisses populaires - Chateau, Jean-Pierre (L'Actualité économique)

(untitled) (HEC Montréal, 1977)
AbstractConsidering the Caisses populaires as a financial system, we propose an econometric model of its consolidated balance sheet built around the following four major blocks. The first one presents a dynamic sub-model of the Caisses' asset portfolio, which emphasizes their intermediation among assets on the basis of the latter interest rates. In a second block, these rates are endogenized with respect to the key variables of both the real and monetary sectors of the economy. On the liability side, the Caisses' deposit market is dealt with in a third block, namely a demand for deposits or flow equation and a supply of deposits or rate setting operation. Finally, adjustment equations for the balance sheet items not already considered, are grouped in a fourth block. The overall model is dynamized through the deposit equation.From the model's econometric estimation, we arrive at the following conclusions about financial management and liquidity policies. On the asset side of the balance sheet, the Caisses aim mainly at satisfying their members' needs for mortgages and, to a lesser but growing degree, for consumer loans. Next, for the funds remaining after satisfying internal needs, the institution proceeds to some sort of secondary, medium-term intermediation, then preferring quasi-liquid and higher yielding bonds to reserves. On the liability side, the Caisses seem to set their rate on deposits on the basis of the one for chartered banks (price leadership) as well as on the basis of the most representative asset rates, i.e. the ones on consumer and mortgage loans. Finally, the public demand for the Caisses' deposits, is more a function of the borrowing privileges offered to the members than of the intrinsic competitive rate paid on them.